Determinan Keluhan Carpal Tunnel Syndrome (CTS) Supir Angkutan Umum Terminal Amplas Tahun 2024 - Muflih Muflih; Yulia Syahputri (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
According to the International Labour Organization (ILO), in 2013, Carpal Tunnel Syndrome (CTS) was almost always found in cases of occupational diseases in various countries. Meanwhile, data from the Occupational Safety and Health Administration (OSHA) in 2014 reported that approximately 900,000 cases of CTS occur among workers each year. This study aims to analyze the factors associated with CTS complaints among public transportation drivers at Terminal Amplas in 2024. The method used is an analytical survey with a cross-sectional approach. The study population consists of 40 public transportation drivers with route number 135, where the entire population was used as the sample. Data analysis was conducted using univariate and bivariate analysis with the chi-square statistical test. The results of the study indicate a significant relationship between CTS complaints and the variables of repetitive movements (p=0.009), years of service (p=0.007), working hours (p=0.000), and age (p=0.016). Meanwhile, smoking habits (p=0.250) were not significantly associated with CTS complaints.